3x+19=-36

Simple and best practice solution for 3x+19=-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+19=-36 equation:


Simplifying
3x + 19 = -36

Reorder the terms:
19 + 3x = -36

Solving
19 + 3x = -36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-19' to each side of the equation.
19 + -19 + 3x = -36 + -19

Combine like terms: 19 + -19 = 0
0 + 3x = -36 + -19
3x = -36 + -19

Combine like terms: -36 + -19 = -55
3x = -55

Divide each side by '3'.
x = -18.33333333

Simplifying
x = -18.33333333

See similar equations:

| t+(-4)=10 | | 2(-6v-1)=33-5v | | a+1(1/4)=2(7/10) | | 2y=3x-18 | | x^3-5x^2+4x+10=0 | | -8n+11=-7n-18 | | -28x^5-4x^4= | | -8x-2=-2(4x+1) | | r+25-5= | | x-0.7=10 | | 3(x+2)=x-15 | | -1+(-8)= | | 2=y/5-8 | | 50-30x=75 | | -2y-12=4y+24 | | -7(c+9)=9(c-5)-14c | | 10/3+8= | | k-31=5(1-7k) | | 4n+3=n-17 | | y^2=12y-35 | | 5y-1=2y+5 | | ABD=180(5y+1) | | 3not=6 | | s^2+45=0 | | 0.7=z+0.5 | | 5x-3=4(x+2) | | 4(1+4x)=30+3x | | -4(d-4)+2(d-2)=10/3 | | 12+3y=9 | | 6t-3=-7 | | 2(x-1)=48 | | a+7+3b+3a-2b= |

Equations solver categories